2020
DOI: 10.1136/bmjdrc-2019-001099
|View full text |Cite
|
Sign up to set email alerts
|

High or low glycemic index (GI) meals at dinner results in greater postprandial glycemia compared with breakfast: a randomized controlled trial

Abstract: IntroductionWhile circadian control of glucose metabolism is well known, how glycemic index (GI) of carbohydrate-rich meals interacts with time of consumption (breakfast or dinner) to influence postprandial (PP) glucose homeostasis is less well established. The objective of the study was to assess markers of PP glucose homeostasis following high or low GI test meals (TM) consumed either at breakfast or at dinner and following consumption of the subsequent standardized meals (SSM).Research design and methodsRan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…On the other hand, their results indicated a greater improvement in iAUC following a low GI meal in the morning and concluded that low GI foods are of less value for glycemic control in the evening than the morning [ 53 ]. Haldar et al found a similar relative reduction in glucose iAUC following a low versus high GI meal for breakfast and dinner [ 54 ]. A greater detrimental effect of the consumption of high carbohydrate content and high GI meals in the evening may partially be attributed to the circadian control of glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, their results indicated a greater improvement in iAUC following a low GI meal in the morning and concluded that low GI foods are of less value for glycemic control in the evening than the morning [ 53 ]. Haldar et al found a similar relative reduction in glucose iAUC following a low versus high GI meal for breakfast and dinner [ 54 ]. A greater detrimental effect of the consumption of high carbohydrate content and high GI meals in the evening may partially be attributed to the circadian control of glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported second‐meal effects in GI measurement, that is, the extension of metabolic effects of the previous meal to the glycemic response of subsequent meal (Wolever et al., 1988). The second‐meal effect has been shown to be impacted by prior meal macronutrient composition (Meng et al., 2017), the GI/GL of previous meal, and the time between the previous and subsequent meals (Haldar et al., 2020; Jenkins et al., 1982; Wolever et al., 1988).…”
Section: Considerations In Developing Ivivc Of Starch‐based Foods With Gastric Digestionmentioning
confidence: 99%
“…Peak glucose after breakfast and lunch in group B was higher than in the other two groups, but peak glucose levels after dinner and time to peak after meals did not differ among the three test days. Many factors can influence postprandial glucose, including the circadian clock, meal timing, and activity [36][37][38]. The peak postprandial glucose after dinner in group B was higher than in groups A and C after dinner; however, the difference did not reach statistical significance, and we believe this finding may be related to the following factors.…”
Section: Discussionmentioning
confidence: 69%